Effects of Land Misallocation on Capital Allocations in India - Duranton, Gilles; Ghani, Ejaz; Goswami, Arti Grover; Kerr, William R. (World Bank, Washington, DC, 2015)
Growing research and policy interest focuses on the misallocation of output and factors of production in developing economies. This paper considers the possible misallocation of financial loans. Using plant-level data on the organized and unorganized sectors, the paper describes the temporal, geographic, and industry distributions of financial loans. The focus of the analysis is the hypothesis that land misallocation might be an important determinant of financial misallocation (for example, because of the role of land as collateral against loans). Using district-industry variations, the analysis finds evidence to support this hypothesis, although it does not find a total reduction in the intensity of financial loans or those being given to new entrants. The analysis also considers differences by gender of business owners and workers in firms. Although potential early gaps for businesses with substantial female employment have disappeared in the organized sector, a sizeable and persistent gap remains in the unorganized sector.